Influence of the Al content on the phase transformations in Cu-Al-Ag alloys - Adorno, A. T. [UNESP]; Benedetti, Assis Vicente [UNESP]; Silva, R. A. G. da [UNESP]; Blanco, M. [UNESP] (Editora Unesp, 2003)
A influência da concentração de Al nas transformações de fase em ligas de Cu-Al-Ag foi estudada por análise térmica diferencial clássica (ATD), microscopia óptica (MO) e difratometria de raios X (DRX). Os resultados indicaram que o aumento no teor de Al e a presença de Ag diminuem a velocidade da reação de decomposição da fase b1 e contribuem para o aumento da temperatura desta transição, diminuindo assim o intervalo de estabilidade da fase perlítica, resultante da reação de decomposição.

The influence of the Al content on the phase transformations in Cu-Al-Ag alloys was studied by classical differential thermal analysis (DTA), optical microscopy (OM) and X-ray diffractometry (XRD). The results indicated that the increase in the Al content and the presence of Ag decrease the rate of the b1 phase decomposition reaction and contribute for the raise of this transition temperature, thus decreasing the stability range of the perlitic phase resulted from the b1 decomposition reaction.
Influência da concentração de Al nas transformações de fase em ligas de Cu-Al-Ag
Keywords: transformações de fase; transformação martensítica; ligas de Cu-Al-Ag; phase transitions; martensitic transformation; Cu-Al-Ag alloys